Elimination profile of triamcinolone hexacetonide and its metabolites in human urine and plasma after a single intra‐articular administration. Issue 11 (17th June 2019) - Coll, Sergi; Matabosch, Xavier; Llorente‐Onaindia, Jone; Carbó, Marcel·li; Pérez‐Mañá, Clara; Monfort, Nuria; Monfort, Jordi; Ventura, Rosa
Abstract: Triamcinolone hexacetonide (THA) is a synthetic glucocorticoid (GC) used by intra‐articular (IA) administration. GCs are prohibited in sports competitions by systemic routes, and they are allowed by other routes considered of local action (IA administration, among others). The aim of the present work was to study the metabolic profile of THA in urine and plasma following IA administration. Eight patients (4 males and 4 females) with knee osteoarthritis received an IA dose of THA (40 mg) in the knee joint. Spot urine and plasma samples were collected before injection and at different time periods up to day 23 and 10 post‐administration, respectively. The samples were analysed by liquid chromatography‐tandem mass spectrometry. Neither THA nor specific THA metabolites were detected in urine. Triamcinolone acetonide (TA) and 6β‐hydroxy‐triamcinolone acetonide were the main urinary metabolites. Maximum concentrations wereobtained between 24 and 48 h after administration. Using the reporting level of 30 ng/mL to distinguish allowed from forbidden administrations of GCs, a large number of false adverse analytical findings would be reported up to day 4. On the other hand, TA was detected in all plasma samples collected up to day 10 after administration. THA was also detected in plasma but at lower concentrations. The detection of plasma THA would be an unequivocal proof to demonstrate IA use of THA. A reversible decrease was observed in plasma concentrations of cortisol in some of the patients, indicating a systemic effect of the drug. Abstract : Triamcinolone hexacetonide (THA) can be detected in plasma which is an unequivocal proof of its use. In urine, the same metabolites as for triamcinolone acetonide are detected. Intraarticular use of THA shows systemic effect.